PENGARUH MEDIA SOSIAL TERHADAP KRISIS AKHLAK PESERTA DIDIK - Ibnu Chudzaifah; Fitri Rahmayanti (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2022)
The purpose of this study is to identify and determine the influence of social media on the moral crisis of class VIII students at Muhammadiyah Al- Amin Middle School, Sorong City. This type of research is quantitative with a descriptive approach and uses a comparative method (Ex Post Facto). The population in the study were students of class VIII which were divided into class VIII A, B, C, D and E, totaling 156 students. For a sample of 113 respondents taken from all class VIII. The research instrument used a questionnaire / questionnaire with a Likert scale. The data that the researchers obtained were then processed using the help of Microsoft Exel 2016 and the SPSS application for Windows Version 22.Based on the results of research at Muhammadiyah Al-Amin Middle School, Sorong City, it shows that social media has an influence on the moral crisis of class VIII students. This can be seen from the rxy value of 0.595% and the coefficient of determination r2 (xy) of 0.354 and tcount of (60.796 > 3.93), based on the coefficient of determination r2 (xy) of 0.354 meaning that 35.4% of the moral crisis is influenced by social media , while the remaining 64.6% is influenced by other factors, for example by the environment, association, character education from parents and teachers